MENUJU SUATU TEOLOGI PERSAHABATAN - Renwarin, Paul Richard (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2019)
What can Christian Theology contribute for Indonesian citizen? That is the leading question for this elaboration and theological reflection on the patterns of relationship among Indonesian people. Living in the context of various cultures, religions, various types of land-islands-archipelago, people take into account two categories to relate one another, namely kinship and friendship. Kin relationship (=bersaudara, having blood relation, coming from the same ancestors, the same genealogy) dominates the way to relate one another. Although the categorization of kin is limited only to those from the same genealogy, this type of category is applied to those outside the genealogy, such as in the expression, ‘we are family’, kita semua bersaudara. This ideal of relationship among the citizens is promoted to bridge the various differences (=bhinneka), though all realize that the unity (=ika) is always in danger and fragile. Another recognized categorization of relationship among the people is friendship (=sahabat, teman, mitra, partner, kolega, pela gandong, semangat korps, etc), which acknowledges and accept the difference among those from different genealogies, cultures, religions, but it is not seen as limitation to be together and act together. Therefore, Theology has to develop the idea of Christian friendship (Yoh 15: 13-15) along with the one of brotherhood, fraternity, in order to build communion among the citizens.